ВЗАИМОСВЯЗЬ ИНТЕРНЕТ-ЗАВИСИМОСТИ И ОСОБЕННОСТЕЙ ЛИЧНОСТИ У ПОДРОСТКОВ - Татьяна ГРАУР (Studia Universitatis Moldaviae: Stiinte ale Educatiei, 2020)
Интернет-зависимость широко распространена в современном обществе, а новые цифровые технологии с поразительной скоростью завладевают миром детей и подростков, являющихся наиболее уязвимыми для формирования патологической увлеченности интернетом, что и определяет научный интерес к данной проблеме. В статье представлены результаты исследования особенностей интернет-зависимости и личностных черт у подростков.   THE RELATIONSHIP OF INTERNET DEPENDENCE AND PERSONALITY TRAITS IN ADOLESCENTS Internet addiction is widespread in modern society, and new digital technologies are capturing with astonishing speed the world of children and adolescents, who are most vulnerable to the formation of pathological enthusiasm for the Internet, which determines the scientific interest to wards this problem. This article presents the results of a study based on the characteristics of Internet addiction and personality traits in adolescents.